Graphical Representation of Solids - An Important Issue in Teaching Technical Drawing - Clinciu, Ramona (Applied Mechanics and Materials, 2013)
The proposed paper presents applications developed in 3D Studio MAX programme. These applications have frequent use in teaching technical drawing and they illustrate, by means of the mapping techniques developed and by the animation facilities of this programme, the methods for constructing and modelling different types of parts and their appropriate orthographic projections, being a helpfull tool for enabling the development of the spatial abilities of the students.Graphical representation of solids is very important in teaching technical drawing and the applications developed on this purpose combine the facilities of 3D Studio MAX program the rendering, mapping and animation techniques with the experience of the author in teaching graphical subjects. In the applications developed Multi/Sub-Object materials are defined and assigned to different surfaces of an object for illustrating and emphasizing the appropriate features of any type of part that is usually met in engineering. The increased realism of the scenes created in the above mentioned programme help students understand the shapes of solids and to corroborate the orthographic projections of parts with the three dimensional view of the parts considered.The applications presented help students increase their spatial abilities, by helping them understand the connection between the orthographic projections of a part - the minimum number of projections needed for defining the part, and the appropriate 3D/axonometric projection of the part. At the same time, the applications presented enable the explanations to be more attractive for the students, such as to increase their interest in the subject.